Kinerja Pelayanan Publik di Pemda Kabupaten dan Kota se-Jawa - Wulandari, Putri (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
A written local autonomy policy in regulation of no 32 year 2004 states that the local government requires the improvement quality of public services and society prosperity. This reserarch purpose was to measure the public services quality, both in regency and city, those included three sectors (education, healthiness, and infrastructures). The method of this research was a descriptive-quantitative method by using questionnaire spreaded into 120 regencies and cities in Java. The data was analyzed to determine public service index (IPP) in the region. The highest region in public service index, especially in education, halthiness, and infrastructures were Klaten regency, Madiun, and Tegal. The lowest region in public service index, especially in education, halthiness, and infrastructures were Batu (Malang), Madiun regency and Banjarnegara regency. The region with highest public service index was Klaten regency and the lowest was Batu (Malang).